2015
DOI: 10.1111/1462-2920.12955
|View full text |Cite
|
Sign up to set email alerts
|

Marine protist diversity in European coastal waters and sediments as revealed by high‐throughput sequencing

Abstract: Summary Although protists are critical components of marine ecosystems, they are still poorly characterized. Here we analysed the taxonomic diversity of planktonic and benthic protist communities collected in six distant European coastal sites. Environmental deoxyribonucleic acid (DNA) and ribonucleic acid (RNA) from three size fractions (pico‐, nano‐ and micro/mesoplankton), as well as from dissolved DNA and surface sediments were used as templates for tag pyrosequencing of the V4 region of the 18S ribosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
355
4
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 351 publications
(398 citation statements)
references
References 65 publications
20
355
4
5
Order By: Relevance
“…Samples from European near-shore marine sites (see Supplementary Code 1 for coordinates of each sample) came from the BioMarKs consortium 28,56 . We re-sequenced the samples here to obtain deeper sequencing.…”
Section: Marine Samplesmentioning
confidence: 99%
“…Samples from European near-shore marine sites (see Supplementary Code 1 for coordinates of each sample) came from the BioMarKs consortium 28,56 . We re-sequenced the samples here to obtain deeper sequencing.…”
Section: Marine Samplesmentioning
confidence: 99%
“…Originally, most of the studies based on metabarcoding focused on prokaryotes (e.g., Sogin et al, 2006;Gilbert et al, 2009;Brazelton et al, 2010;Salazar et al, 2016), but, more recently, eukaryotes have also been investigated, including marine protists (e.g., Amaral-Zettler et al, 2009;Stoeck et al, 2010;Logares et al, 2014a;de Vargas et al, 2015;Massana et al, 2015) and metazoans (Thomsen et al, 2012;Lindeque et al, 2013;Hirai et al, 2015;Pearman and Irigoien, 2015). The development of highthroughput sequencing (HTS) technologies and of standardized procedures could allow metabarcoding analyses to be included in routine monitoring programmes (Visco et al, 2015;Zaiko et al, 2015a,b).…”
Section: Use Of Metabarcoding To Study Marine Biodiversitymentioning
confidence: 99%
“…Both V4 and V9 are considered suitable regions for biodiversity studies given their great variability and the combination of high and low entropy in these sections, which allows forgood primer binding (Behnke et al, 2011;Hadziavdic et al, 2014;Tanabe et al, 2016). They also have been widely used in molecular diversity studies, so the research community knows the advantages and limitations of both regions (AmaralZettler et al, 2009;Stoeck et al, 2010;Massana et al, 2015). In fact, we overcame one of the main limitations of the V9 region, which is its short length (Amaral-Zettler et al, 2009;Pawlowski et al, 2011), by sequencing the V8 region as well.…”
Section: Discussionmentioning
confidence: 99%
“…PCR amplification of either the V4 or V8-9 regions of 18S rDNA were performed as previously described (Kim et al, 2016). Both V4 and V8-9 regions of the 18S rRNA gene were sequenced because of their extensive use for eukaryotic diversity (Nickrent and Sargent, 1991;Amaral-Zettler et al, 2009;Massana et al, 2015) and to compensate the existing primer bias of each region. Amplicon libraries were prepared as in Kim et al (2016) (further details about library preparation can be found in Supplementary Table).…”
Section: Dna Extraction and Next-generation Sequencingmentioning
confidence: 99%
See 1 more Smart Citation